2021
DOI: 10.1002/rra.3776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cascade reservoirs on the transformation of nitrogen in pore water of sediments in the Lancang River

Abstract: In the mainstream of the Lancang River, eight cascade dams have been constructed. In order to find the effects of the cascade reservoirs on the transformation of nitrate (NO3‐N) and ammonium (NH4‐N) in pore water of sediments, a field survey was carried out both in the upper natural river reach (NRR) and cascade reservoirs reach (CRR) of the Lancang River from January 10 to 20, 2018. The results indicated that (1) in the NRR, NO3‐N concentrations in sediment pore water were higher than those in the CRR, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The accumulation of ammonium-N in anoxic environments like wetlands (e.g., Jahangir et al, 2017;Rahman et al, 2019;and Zhao et al, 2021) and stream-riparian margin sediments (Duval & Hill, 2007) has been reported before. Jahangir et al (2017) and Zhao et al (2021) attributed the ammonium accumulation to DNRA, while Duval and Hill (2007) attributed it to anaerobic mineralization of buried organic material and suppression of nitrification.…”
Section: Updated Model Of N Changes In Riparian Soils Following Dam Removalsupporting
confidence: 52%
See 3 more Smart Citations
“…The accumulation of ammonium-N in anoxic environments like wetlands (e.g., Jahangir et al, 2017;Rahman et al, 2019;and Zhao et al, 2021) and stream-riparian margin sediments (Duval & Hill, 2007) has been reported before. Jahangir et al (2017) and Zhao et al (2021) attributed the ammonium accumulation to DNRA, while Duval and Hill (2007) attributed it to anaerobic mineralization of buried organic material and suppression of nitrification.…”
Section: Updated Model Of N Changes In Riparian Soils Following Dam Removalsupporting
confidence: 52%
“…Recent work of Zhao et al. (2021), for cascade dam reservoirs in China, suggest that anoxic conditions associated with small dams could increase the sediment pore water concentrations of ammonium‐N (at the cost of nitrate‐N) and the accumulated sediment pore water ammonium could diffuse into overlying waters posing a water quality risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reservoirs have significantly altered the natural hydrological and ecological processes in rivers. Zhao, Wang, Wang, Yang, and Liu (2021) present the results of a field survey in both natural river reaches and reaches impacted by cascade reservoirs to investigate their effects on the transformation of nitrate and ammonium in pore water of sediments. The results showed that cascade reservoirs could promote denitrification, restrain nitrification in sediment pore water and increase the risk of ammonium emission from the sediments.…”
Section: Identifying Mechanisms Influencing Changementioning
confidence: 99%